European Urban Traditions: An Anthropologist's View on Polis, Urbs, and Civitas. (August 2016) - Prato, Giuliana B.
The argument developed in this article originates from the reflection that what constitutes a city or what is meant by urban are differently understood in different parts of the world and by different scholars. Thus, I first address the problematic of incommensurability. I argue that this key issue in the philosophy of science is central to how the debate on urban anthropology has developed. Then I ask whether this problematic extends to cross-disciplinary debate among the contemporary social sciences and what relevance the resulting understanding of the city has outside the academic world. I maintain that social analysis should endeavour to bring out the political, economic, and socio-cultural complexity of urban life. Having carried out research in urban Europe, I offer an analysis of the city that encompasses the meaning of urbs, polis, and civitas . Finally, I discuss the epistemological significance of urban ethnography, drawing on my field research in Brindisi, a South-Italian city.